2020
DOI: 10.36941/ajis-2020-0120
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers in Intercultural Communication: A Case Study on Agricultural Idioms in English, Ukrainian and Chinese

Abstract: The paper deals with the case study, focused on exploring certain problems in intercultural communication of Ukrainian and Chinese students in the academic environment of Sumy National Agrarian University. The participants of the ethnographic-linguistic stage of the experiment learned, interpreted and compared the phraseological funds of the Chinese, Ukrainian and English languages, displaying the conceptual sphere “Agriculture”, in order to find out similarities and divarications in the outlook of people, eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…В. С. Пащук поділяє загальні вміння ММ майбутніх вчителів АМ на групи: 1) уміння реалізовувати комунікативний намір адекватно завданню та умовам спілкування; 2) уміння логіко-композиційної побудови висловлювання у відповідності до композиційно-мовленнєвих форм монологу; 3) комбінаційні вміння 16 . Спеціальними уміннями ММ вважають уміння: з'єднувати та логічно структурувати декілька мовленнєвих зразків; повно висловлюватись відповідно до комунікативної ситуації та теми; правильно в аспекті системи та норм АМ оформити своє висловлювання мовними засобами відповідного рівня складності; оптимально використовувати мовний матеріал з урахуванням вимог рівня навчання (програми); оптимально використовувати вивчений матеріал, свідомо переносити раніше набуті знання, навички та вміння на нову ситуацію; залучати до викладу певної теми матеріал суміжних тем, розширюючи і поглиблюючи її, комбінуючи і варіюючи матеріал за формою та за змістом 17 .…”
Section: мета зміст та контроль формування компетентності в монологіч...unclassified
“…В. С. Пащук поділяє загальні вміння ММ майбутніх вчителів АМ на групи: 1) уміння реалізовувати комунікативний намір адекватно завданню та умовам спілкування; 2) уміння логіко-композиційної побудови висловлювання у відповідності до композиційно-мовленнєвих форм монологу; 3) комбінаційні вміння 16 . Спеціальними уміннями ММ вважають уміння: з'єднувати та логічно структурувати декілька мовленнєвих зразків; повно висловлюватись відповідно до комунікативної ситуації та теми; правильно в аспекті системи та норм АМ оформити своє висловлювання мовними засобами відповідного рівня складності; оптимально використовувати мовний матеріал з урахуванням вимог рівня навчання (програми); оптимально використовувати вивчений матеріал, свідомо переносити раніше набуті знання, навички та вміння на нову ситуацію; залучати до викладу певної теми матеріал суміжних тем, розширюючи і поглиблюючи її, комбінуючи і варіюючи матеріал за формою та за змістом 17 .…”
Section: мета зміст та контроль формування компетентності в монологіч...unclassified
“…Globalization urges the students to pursue higher studies in developed economies in order to learn advanced education tools to compete in the world. One of the common barriers faced by countries having not English as their native language is communication (Fomenko et al, 2020;Gardner, 2020). Thus, the students approach the local linguistic schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study addresses some gaps that exist in the literature like (1) being one of the important topics like English education system and capital and individual performance although researched although but still not reached its peak, (2) Fomenko et al (2020) investigated the barrier of intercultural communication, whereas the present student has employed number of variables like resistance to innovation, students lack of interest, students demotivation and English language and check the model in Chinese educational institutions, (3) Badrkoohi (2018) investigated the association between demotivation and intercultural communication, whereas this study adds the variable and also checks the mediation effect in Chinese perspective, (4) Saeed et al (2018) worked on the students interest factors, whereas this study adds the variables like resistance to innovation, students demotivation, students demotivation, and English language and checks the model with new data set; this study checks the model in Chinese perspective with new data set, (5) Kusdemir and Bulut (2018) worked on the student motivations, whereas this study takes the students' demotivation and tests the model in Chinese educational instructions, and (6) a study by Schröer (2021) also examined the innovation role on the education system and suggested that the upcoming articles should add other factors to predict education system, and this article uses the resistant to innovation and lack of intercultural communication to predict the English education system. The significances of this study are as follows: (1) it highlights the importance of intercultural communication and education system in countries where the native language is not English like Chinese, (2) helps professional to revamp their policies for the betterment of linguistic education like English in China, and (3) helps the researchers to identify the linguistic importance for any country not having English as their mother language.…”
Section: Introductionmentioning
confidence: 97%
“…The works of such outstanding domestic and foreign researchers as P. Bożyk [28][29][30][31][32][33][34][35][36][37][38]. The lack of scientific developments, devoted to the outlined problem with an emphasis on new promising areas of research, determined the relevance and choice of the research topic.…”
Section: Literature Reviewmentioning
confidence: 99%